STEM in physics learning: Benefits, challenges, and future research opportunities - Saripah, Siti Awaliyah; Wibowo, Firmanul Catur; Astra, I Made; Budi, Esmar (Universitas PGRI Kanjuruhan Malang, 2025)
Data-driven approaches have emerged for several reasons, including the continuous evolution of the education sector. Across various educational fields and levels, STEM integration in learning has been implemented. Therefore, this journal presents data on the role of STEM in Physics Education. The research discussion on the use of STEM in Physics learning can also serve as a coherent background and literature review for readers who wish to conduct further research. The literature review is conducted by considering the bibliometric perspective of publications related to STEM integration in Physics learning. This study supports the journal's importance by highlighting the need for reputable journal publications. The analysis aims to provide a comprehensive bibliography and review of STEM's use in Physics learning, utilizing the